Analisis Kondisi Dan Penanganan Kerusakan Jalan Dengan Metode PCI Dan Bina Marga (Studi Kasus Jalan Simpang Kurun Sei Hanyo Petak Bahandang Gunung Mas) - Ramadhan, Moh Biagi; Supiyan, Supiyan; Elvina, Ina (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2025)
The existence of road infrastructure is very important to facilitate the functioning of the transportation system, economic activities, and public movement effectively. One of the major problems in the field of infrastructure is road damage. Damage to the road surface due to vehicle loads and environmental conditions requires appropriate maintenance strategies to maintain its operational capabilities. The Simpang Kurun – Sei Hanyo – Petak Bahandang road in Gunung Mas Regency is one of the main routes that experiences damage with various degrees of severity, thus requiring a proper handling analysis. This study aims to analyze the types of road damage, evaluate the surface condition of the road, and identify suitable maintenance methods, including cost estimates for repairs. The research methods used include the Pavement Condition Index (PCI) and the Bina Marga approach. Traffic volume data were recorded during visual surveys. The average pavement condition index (PCI) is 57.5 (considered fair), with an average daily traffic volume (ADT) of 1,006 vehicles per day (classified as traffic class 4), and a condition value of 1.4 according to the Bina Marga method with a priority index of 11.6 indicating the need for routine maintenance. The total maintenance cost is estimated to reach Rp78,689,226.47. Based on these results, the recommended strategy includes routine maintenance for minor damages, patching and overlay for moderate damages, and reconstruction of the pavement on segments with severe damage. In conclusion, the road conditions in the study area require serious attention with a combination of short-term and long-term measures to improve the quality of road service and support the mobility of the people in Gunung Mas District.